Catalyzing Growth: The Power of Innovation in Organizational Dynamics - Erno Rusadi, Bobi; Wenny Sitanggang, Tantri; Asbari, Masduki (Takaza Innovatix Labs Ltd., 2024)
This study examines the impact of Innovation Practices and Organizational Dynamics on Organizational Growth at PT. Contindo Raya, with a focus on the mediating role of Employee Engagement. Utilizing a quantitative research design and random sampling of 70 employees, data were analyzed using SMART PLS to assess direct and indirect effects. The findings reveal that both Innovation Practices and Organizational Dynamics significantly influence Organizational Growth, with Employee Engagement acting as a critical mediator in these relationships. Innovation Practices directly enhance Employee Engagement, which in turn drives growth, while Organizational Dynamics also contribute to growth through their impact on Employee Engagement. These results underscore the importance of integrating innovative practices and improving organizational dynamics to foster a more engaged workforce and support sustainable growth. This study provides actionable insights for PT. Contindo Raya to leverage these factors for achieving competitive advantage and long-term success.